Técnicas de manejo conductual para disminuir las conductas disruptivas en los niños y niñas del sexto año paralelo B, de la escuela de educación básica Ciudad de Loja, 2019 – 202 - Robles Vega, Mónica Alexandra (2020)
Disruptive behaviors are inappropriate behaviors of students that prevent keeping pace with the class, hinder the work of teachers and can interfere in the learning process, becoming a problem in school coexistence, therefore, this research deals with on: BEHAVIORAL MANAGEMENT TECHNIQUES TO DECREASE DISRUPTIVE BEHAVIORS IN THE SIXTH YEAR PARALLEL B, OF THE BASQUE EDUCATION SCHOOL CIUDAD DE LOJA, 2019 - 2020. The objective of this research was to implement behavioral management techniques to decrease the disruptive behaviors in boys and girls of the sixth parallel year b. The research responded to a descriptive study, with a cross-sectional and quasi-experimental design; based on the methods: scientific, inductive, deductive, analytical, synthetic and statistical of the linear correlation coefficient of Karl Pearson (r). The CDIS disruptive behavior scale was applied to the sample of 31 students. The results that we were able to collect in the (pre-test) is that 91.2% of the students presented in a greater quantity the characteristics of disruptive behaviors in the classroom such as contempt of the teacher, non-compliance with tasks and alterations in the classroom; After seeing the execution of the alternative proposal and applying the (post-test), the findings are significant, since the results show us a lower percentage, 32.8% of the students presented characteristics of the disruptive behaviors mentioned above. the classroom. Subsequently, with the help of the statistical method of Pearson's linear correlation coefficient, we obtained the following results in the variable contempt of the teacher, we obtained a value of r = 0.54, which means an average positive correlation, in the variable of non-compliance with tasks, we obtained a value of r = 0.70 which means mean positive Correlation and in the classroom disturbances variable we obtained a value of r = 0.79 which means considerable positive correlation. Therefore, it is concluded that the behavioral management techniques helped to greatly reduce the characteristics of disruptive behaviors that occurred in the classroom, so the application of the proposal is validated since these workshops did allow us to change of attitudes and favorable characteristics against this problem that is disruption.